2014
DOI: 10.1007/s10549-014-3034-3
|View full text |Cite
|
Sign up to set email alerts
|

Breast implant-associated anaplastic large cell lymphoma: sensitivity, specificity, and findings of imaging studies in 44 patients

Abstract: Current imaging with US, CT, MR, and PET appears suboptimal in the detection of an imaging abnormality associated with BIA ALCL. This under diagnosis may reflect a lack of awareness of this rare entity suggesting the need for better understanding of the spectrum of imaging findings associated with BIA ALCL by breast imagers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
118
0
19

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 29 publications
0
118
0
19
Order By: Relevance
“…One third of patients present with a mass which may indicate a more aggressive clinical course. Adrada and colleagues reviewed 44 BI-ALCL patients with imaging studies and reported on the sensitivity/specificity for detecting an effusion using ultrasound (84%/75%), computerized tomography (55%/83%), magnetic resonance imaging (82%/33%), and positron emission tomography (38%/83%) (59). Additionally, the sensitivity/specificity to detect a BI-ALCL mass was reported for ultrasound (46%/100%), computerized tomography (50%/100%), magnetic resonance imaging (82%/33%), and positron emission tomography (64%/88%).…”
Section: Presentation and Diagnosis Of Bi-alclmentioning
confidence: 99%
“…One third of patients present with a mass which may indicate a more aggressive clinical course. Adrada and colleagues reviewed 44 BI-ALCL patients with imaging studies and reported on the sensitivity/specificity for detecting an effusion using ultrasound (84%/75%), computerized tomography (55%/83%), magnetic resonance imaging (82%/33%), and positron emission tomography (38%/83%) (59). Additionally, the sensitivity/specificity to detect a BI-ALCL mass was reported for ultrasound (46%/100%), computerized tomography (50%/100%), magnetic resonance imaging (82%/33%), and positron emission tomography (64%/88%).…”
Section: Presentation and Diagnosis Of Bi-alclmentioning
confidence: 99%
“…1,2 We are in the process of completing a cohort study of breast implant-associated ALCL in Australia and New Zealand to calculate true implant-specific risk based on actual sales data. General requirements for informed consent.…”
Section: Office For Human Research Protections Code Of Federalmentioning
confidence: 99%
“…2 The authors stated that the timing of reconstruction after wide local excision is still controversial, and that in some centers the reconstruction is delayed. In the meantime, if we continue to use textured implants, the data point to a much higher rate of potential contamination.…”
Section: Office For Human Research Protections Code Of Federalmentioning
confidence: 99%
“…Its occurrence usually correlates with the age of the implant and it is most frequently observed after 10 years. In 2011, the FDA reported a possible association of breast implants with anaplastic large cell lymphoma [7], but the relationship has yet to be confirmed in a prospective study.…”
Section: Breast Implants General Considerationsmentioning
confidence: 99%